Electrodeposition of Co(OH)2 Film and its Conversion into Co3O4 Film for Supercapacitors - Li, Yanhua; Chen, Qiyuan (Asian Journal of Chemistry, 2012)
Co(OH)2 film is prepared by electrodeposition and then Co3O4 film is obtained by calcining Co(OH)2 film. Capacitive properties of these films are measured. The results show that the specific capacitance of Co(OH)2 film, Co3O4 film obtained by calcining at 200 and 300 ºC at the current density of 0.2 A g-1 are 153.4, 150.4 and 129.1 F g-1, respectively. The specific capacitance retention ratio of three film electrodes is above 97 % at the current density range from 0.2-1.0 A g-1. The specific capacitance retention ratio of above 88 % is obtained in three film electrodes when the current density increases from 0.2-2.0 A g-1. These values are higher than those of Co3O4 film prepared by chemical bath deposition.